New microscope produced by Lambda Praha Co. applicable to field studies of microorganisms - Zizka, Z (Folia microbiologica, 2008)
A new microscope produced by the company Lambda Praha, applicable to field studies, was used for the observation of biofilms growing on stones and rocks of the Red Sea beach at Sharm El Sheikh resort in Egypt. The microscope was equipped with a novel LED illumination system, independent of sunlight as the light source, and an attachable mechanical stage making possible a precise and systematic observation of the preparation. Using this device, black biofilms of cyanobacteria and green biofilms of algae were studied; characteristic sheaths protecting the cells against the intense sunlight were found in cyanobacteria belonging to the genus Lyngbya. Trichomes on phylloids consisting of 3 to 4 cells were observed in algae belonging to the genus Padina, whose nuclei were degraded as a result of apoptosis, which is in contrast to the species Padina pavonia containing visible nuclear residues observed on the shore of the Mediterranean Sea near Lastovo island in Croatia in 2007.
Keywords: sinice; Phaeophyceae; Cyanobacteria; Chlorophyta; Biofilms; mikroskopie; Indian Ocean; Microscopy; geologické sedimenty; Geologic Sediments; Egypt; biofilmy; Indický oceán